Patriarchy between the lines of society: the exposure of the image of women as fruit of male desires - Ramos, Thomas Barrili (Em Perspectiva, 2020)
This research is based on the analysis of the representation of female bodies in the photographs of a brazillian newspaper entitled O Rio Nu, which circulated in the first decades of the twentieth century in the Rio de Janeiro. The research aimed to verify how the patriarchy instituted in Brazilian society ended up expressing itself with the choice of female images, which generated attraction in the male public. These images were resignified to a context of consumption and pornography. The analysis was based on an observation of the iconography of the different elements present in the photographs placed in the journal and the relationship of their possible meanings with the values and characteristics of the Brazilian cultural identity. It was verified how cultural conditions are composing agents for the pattern exposed in erotic representations, as well as the way those bodies were viewed and traded and the male overlap as causing these conditions. These and other factors made it possible to understand that values and customs manifest themselves in every human expression, and that the newspaper analyzed is just another result of patriarchalism deeply rooted in our civilization.